2007
DOI: 10.1371/journal.pgen.0030005
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Exposure In Utero Disrupts Early Oogenesis in the Mouse

Abstract: Estrogen plays an essential role in the growth and maturation of the mammalian oocyte, and recent studies suggest that it also influences follicle formation in the neonatal ovary. In the course of studies designed to assess the effect of the estrogenic chemical bisphenol A (BPA) on mammalian oogenesis, we uncovered an estrogenic effect at an even earlier stage of oocyte development—at the onset of meiosis in the fetal ovary. Pregnant mice were treated with low, environmentally relevant doses of BPA during mid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
330
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(347 citation statements)
references
References 43 publications
15
330
1
1
Order By: Relevance
“…These studies have several limitations, including the analytical methods used and the selection of human subjects. However, studies from rodents suggest that BPA can cause aneuploidy in oocytes (Susiarjo et al 2007) and alter the body weight of offspring resulting from intrauterine transplantation of embryos cultured in media containing BPA (Takai et al 2001). As such, presence of measurable concentrations of unconjugated BPA in follicular fluid is a potential concern.…”
Section: Healthymentioning
confidence: 99%
“…These studies have several limitations, including the analytical methods used and the selection of human subjects. However, studies from rodents suggest that BPA can cause aneuploidy in oocytes (Susiarjo et al 2007) and alter the body weight of offspring resulting from intrauterine transplantation of embryos cultured in media containing BPA (Takai et al 2001). As such, presence of measurable concentrations of unconjugated BPA in follicular fluid is a potential concern.…”
Section: Healthymentioning
confidence: 99%
“…In the cow, estrogen may block follicle activation by inhibiting meiotic progression. Supporting the idea that estrogen can affect meiotic progression, bisphenol A (BPA) treatment of mouse embryos caused defects in meiosis (Susiarjo et al 2007). ESR2 mutants had meiotic defects similar to BPA-treated animals, suggesting that BPA acts as an ESR2 antagonist.…”
Section: Links Between Meiotic Progression and Follicle Formationmentioning
confidence: 99%
“…Bronson et al (1995) revealed aneuploidy in humans from several embryonic stem cell-derived male offspring. Treatment of pregnant mice with low, environmentally relevant doses of BPA during mid-gestation translated into an increase in aneuploid eggs and embryos in the mature female (Susiarjo et al, 2007). A significant difference was found in aneuploidies between hFVIII transgenic and non-transgenic peripheral blood cells (Parkanyi et al, 2004;unpublished observations) but without any deleterious effect on the health or reproduction of animals.…”
Section: Resultsmentioning
confidence: 98%